Determination of Voriconazole in Human Plasma Using RP-HPLC/UV-VIS Detection: Method Development and Validation; Subsequently Evaluation of Voriconazole Pharmacokinetic Profile in Pakistani Healthy Male Volunteers. (23rd September 2021) - Mushtaq, Mehwish; Shah, Yasar; Samiullah,; Nasir, Fazli; Khan, Haroon; Faheem, Muhammad; Nadeem, Atif; Khan, Sundas; Khan, Sumaira Irum; Abbas, Muhammad; Khuda, Fazli; Iftikhar, Tayyaba
Abstract: In this research work, an isocratic, reversed-phase high-performance liquid chromatography-ultraviolet/visible detector method was developed for analysis of voriconazole standard (stock-solution) and in plasma samples. Optimization and validation of the method was carried out as per international guidelines. The method offered a simple liquid–liquid extraction technique, which exhibited best recovery of voriconazole along with fluconazole, i.e., internal standard. Different experimental conditions were tried and ultimately, the best outcomes were accomplished utilizing C-18 Perkin-Elmer® column with particulars of 150 mm length, 4.6 mm inner diameter and 5 μm particle size, protected by an RP-18 Perkin-Elmer® Pre-column guard cartridge with specifications of 10 μm particle size, 30 mm length and 4.6 mm inner diameter, utilizing mobile-phase of acetonitrile-water (ACN: H2O) in proportion of 60: 40 v/v, having a flow rate of 1.5 mL/min, and wavelength of 254 nm. All the analytes were observed to be separated in ≤7 min. A linear calibration curve was obtained at concentration range of 01–10 μg/mL of voriconazole. The correlation coefficient of voriconazole was observed to be 0.999, and average recovery (in percent) was 97.4%, whereas the relative standard deviation value was ≤2%. The lower limit of detection was 0.01 μg/mL, whereas, lower limit of quantification was 0.03 μg/mL, respectively. This developed method provided outstanding results of all validation parameters, i.e., recovery, accuracy, selectivity, precision and reproducibility. The method proposed for voriconazole analysis was applied effectively for further research investigation of voriconazole in human-plasma samples (to assess the pharmacokinetic parameters), pharmaceutical formulations and pharmacokinetic drug–drug interaction's. Graphical abstract: